Step 1: Apply the change of base formula to rewrite the logarithmic expressions.
Using the formula \(\log_a x = \frac{\log x}{\log a}\), the equation is transformed into:
\[
\frac{\log 2}{\log x} + \frac{\log 3}{\log x} + \frac{\log 4}{\log x} = 1
\]
Step 2: Simplify the given equation.
Factor out \(\frac{1}{\log x}\) from the terms:
\[
\frac{1}{\log x} \left( \log 2 + \log 3 + \log 4 \right) = 1
\]
Combine logarithmic terms using the property \(\log a + \log b = \log(ab)\):
\[
\log 2 + \log 3 + \log 4 = \log(2 \times 3 \times 4) = \log 24
\]
Thus, the equation simplifies to:
\[
\frac{\log 24}{\log x} = 1
\]
Step 3: Determine the value of \(x\).
Multiplying both sides by \(\log x\) gives:
\[
\log 24 = \log x
\]
Applying the logarithmic property where \(\log a = \log b\) implies \(a = b\), we get:
\[
x = 24
\]
Final Answer:
\[\boxed{{(C) 24}}\]
Was this answer helpful?
0
0
Top Questions on Logical and Analytical Reasoning Skills